PENGEMBANGAN BUKU AJAR EKOLOGI HEWAN BERBASIS POTENSI LOKAL KAWASAN DANAU TOBA - Retnita Ernayani Lubis; Mimien Henie Irawaty; Ibrohim Ibrohim; Sri Endah Indrawati (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2019)
This research is a development research. The aim of the study was to develop a valid and practical Animal Ecology textbook in the Lake Toba Region. The development research used was using the Thiagarajan 4D model. The results showed that in the define phase a mapping of the basic competencies of Animal Ecology and the material of local potential of the Lake Toba Region was produced. The design phase shows the textbook format that will be developed. The develope stage shows the results of validation by the validator stating that the local potential based Ecology Animal textbook is valid and the results of the student response questionnaire on positive textbooks. Animal Ecology textbooks based on the local potential of Lake Toba produced have met valid and practical criteria.Keywords. Learning Animal Ecology, Local Potential.